Leaf and fruit essential oil compositions of Pimenta guatemalensis (Myrtaceae) from Costa Rica - Chaverri, Carlos (Universidad de Costa Rica, 2015)
Pimenta is a genus of flowering plants in the Myrtaceae family, which has about 15 species, mostly found in the Caribbean region of the Americas. Commonly used for culinary and medicinal purposes, the best known commercial species are allspice, P. dioica (P. officinalis) and bay rum, P. racemosa, but there is little information concerning P. guatemalensis. The aim of the present study was to identify the chemical composition of the leaf and fruit essential oils of P. guatemalensis. The extraction of essential oils of P. guatemalensis growing wild in Costa Rica was carried out by the hydrodistillation method at atmospheric pressure, using a modified Clevenger type apparatus. The chemical composition of the oils was analyzed by capillary gas chromatography-flame ionization detector (GC/FID) and gas chromatography-mass spectrometry (GC/MS) using the retention indices on DB-5 type capillary column. A total of 103 and 64 compounds were identified in the leaf and fruit oils, respectively, corresponding to 96.8% and 86.1% of the total amount of the oils. The leaf oil consisted mainly of eugenol (72.8%), and mono- and sesquiterpene hydrocarbons (18.2%). Among terpenes the major components were b-caryophyllene (8.2%) and terpinolene (3.0%). The fruit oil also consisted mainly of eugenol (74.7%) and minor amounts of oxygenated mono- and sesquiterpenes (7.3%), mainly caryophyllene oxide (3.3%). This is the first report of the chemical composition of the essential oils obtained from this plant species.